Combustion and Performance of Syngas Dual Fueling in a CI Engine with Blended Biodiesel as Pilot Fuel - Hassan, Suhaimi (2017)
Simulated syngas produced from biomass gasification was evaluated in a compression ignition (CI) engine under a dual fueling mode. Syngas is an economical solution with a carbon-neutral system that could replace petroleum diesel fuel. Syngas can be introduced into CI engines through a dual fueling process. However, syngas dual fueling combustion is very complicated because it consists of several combustion phases. In addition, CI engines operating under the syngas dual fueling mode suffer from low performance. Therefore, this study examined the performance of syngas dual fueling in a CI engine with blended biodiesel as pilot fuel. Two types of simulated syngas, namely typical syngas and high hydrogen syngas, were considered.